"[T]hings among the ruins" : les choses contre le roc dans The Song of the Lark et The Professor’s House de Willa Cather - Céline Manresa (Anglophonia)
Exploring the vast expanses of the American wilderness in her fiction, Willa Cather had to find a new mode of nature-writing. Facing the threat of annihilation of discourse and "erasure of personality" in the vastness of the land, the author skilfully adjusts her language to the surface of the landscape. In The Song of the Lark (1915) and The Professor’s House (1925), Cather evokes the hostile yet mesmerizing canyons and mesas of the American Southwest. In order to face the alienating immensity of the landscape, Cather draws on the mediating power of material things and objects harboured in the cliff-dwellings. The radiating presence of sculpted jars, instruments and jewels set in the recesses of the rock reveals the possibility of a gentle insertion of man’s hand in nature. The relics of tools and pottery moulded in the earth or carved in stone by ancient potters become metascriptural emblems. Like a sculptor chiselling marble, the author fashions the raw material of language in order to create a simple and concrete prose linking the literariness of discourse and the literalness of the world. Cather’s crafted writing engages in the physical world. If material things pave the way to a gentle taming of the wilderness, the objects modelled by cliff-dwellers epitomize the homology between the writer’s and the potter’s gestures. Altering her signifiers by referring to natural substances, such as clay, sand, gems and metals, Cather succeeds in creating a harmonious and respectful dialogue between her writing and the surrounding world